ENRICHING MICROTEACHING IN TEACHING ENGLISH TO YOUNG LEARNERS (TEYL): AN ACTION RESEARCH - Gonca Yangın Ekşi; Asuman Aşık (International Online Journal of Education and Teaching, 2015)
This action research is conducted upon noticing the need to provide pre-service teachers of English with a deeper insight into their microteaching demonstrations in TEYL course, which takes place in third year of the teacher training program before the practicum. Regarding the microteachings in TEYL course, the pre-service teachers complained about not being sure how children learn, think and act. Their concerns and dissatisfaction about the performance and feedback stages of microteaching sessions were also acknowledged by the researchers. Thus, 71 pre-service teachers were required to re-conduct their storytelling with target age children and complete a reflection questionnaire. The qualitative analysis of the data reveals that microteachings had some drawbacks in preparing pre-service teachers to the teaching profession. Actual practices with children enabled the pre-service teachers experiencing the natural atmosphere of teaching and developing understanding how children think, learn and react.